Exploring the role of spatial ability in the mental representation of word problems in mathematics - Duffy, Gavin; Sorby, Sheryl; Bowe, Brian (Frontiers in Education, 2024)
Problem solving is important to many activities, both in a learning context and in everyday tasks. We can be challenged to solve what later turn out to be very simple problems. By understanding more about these challenges and what occurs at a cognitive level during the problem-solving process, we can better support the development of problem-solving skills. Spatial ability has been shown to be related to the ability to develop accurate and schematic mental representations of problems during the problem-solving process. The purpose of this study was to examine the role of spatial ability in solving word problems in mathematics among a cognitively diverse sample of engineering students. A set of five word problems, a test of mental rotation and set of five questions testing the core mathematical competencies needed to solve the word problems were administered to 115 first year engineering students. Using a knowledge framework for problem solving, key aspects of representation were extracted from solutions to the word problems and combined to create a mental representation scale. A large and significant correlation was measured between mental rotation and problem representation, larger than the correlation between spatial ability and problem-solving. Mental representation was found to mediate the relation between spatial ability and word problemsolving. This relation was not found to be significantly moderated by core competency in mathematics. For high levels of core competency only, there was an interaction between spatial ability and core competency.